Risk factors for postoperative intracranial infection in Chinese pituitary adenoma patients with endonasal transsphenoidal approach: a Meta-analysis - ZHANG Lating; JIANG Xue; HAN Lin (Yixue xinzhi zazhi, 2025)
Objective To systematically evaluate the risk factors associated with intracranial infections complicating pituitary adenomas resection by transsphenoidal approach. Methods Web of Science, PubMed, Cochrane Library, Embase, Wanfang, CNKI, China Biomedical Literature Database, and VIP database were searched for studies about the risk factors of intracranial infections complicating pituitary adenomas resection with transsphenoidal approach in Chinese patients with pituitary tumors. The search time was from inception to December 2024. Meta-analysis was performed using Stata 16.0 software. Results A total of 37 literatures were included with 12,792 patients involved. The incidence rate of intracranial infections was 7.4%[95%CI(6.0%, 8.8%)]. Meta-analysis showed that Kelly grade>2, intraoperative damage to the diaphragma sellae, secondary surgery, pulmonary infection, intraoperative and postoperative cerebrospinal fluid leakage, intracranial pneumatosis, growth hormone-secreting adenoma, operation time>1 h, postoperative indwelling drain, preoperative hormone use, intraoperative bleeding>120 mL, comorbid diabetes mellitus, and tumor length diameter>3 cm were the risk factors for intracranial infection. Preoperative use of antimicrobial drugs was a protective factor. Conclusion It is necessary for clinical staff to evaluate patients undergoing transsphenoidal pituitary adenoma resection based on the influencing factors of intracranial infection. For high-risk patients, antibiotics can be used before surgery, and timely measures should be taken to reduce the occurrence of intracranial infection after pituitary adenomas resection with transsphenoidal approach.